The Study Of Organizational Culture Associated With Unified Theory Of Acceptance And Use Of Technology Model In Hospitals Of Rasht - Mehrdad Goudarzvand Ghegini; Samaneh Esmaeili (Tehran University of Medical Sciences, 2015)
Background and Aim: The function of any technology in a society depends on the culture of that society. Organizational culture leads to a common understanding and agreement on institutional practices. Meanwhile, it is a powerful barrier to change, especially technological change. This study aims to determine the effect of indicators of organizational culture on the unified theory of acceptance and use of technology in hospitals of Rasht, Gilan Province. Materials and Methods: This is a cross-sectional, descriptive-analytic study . From April to July 2013, 235 questionnaires were completed by health, administrative, financial and educational personnel of Razi, Poursina, and Heshmat Hospitals. For data analysis, such tests as compound reliability test, root mean square of variance, bootstrap test, t-test, and hierarchical regression were applied using Lisrel, PLS and SPSS softwares. Results: Among the components of organizational culture (performance expectancy, effort expectancy, subjective norm, and facilitating conditions), there was a significant relationship only between "performance expectancy and facilitating conditions" and "behavioral inclination and using computers" (P0.05). Conclusion: The results of the study indicate that there is a relationship between organizational culture and application of information technology, and that a unified organizational culture can facilitate and speed up the acceptance and application of information technology.